Navigating the Handover: Reviewing Takeover Requests in Level 3 Autonomous Vehicles - Joel Andrew Miller; Soodeh Nikan; Mohamed H. Zaki (IEEE Open Journal of Vehicular Technology)
Autonomous vehicles (AVs) represent a transformative advance in automotive technology, promising increased safety and efficiency by reducing human error. However, integrating human factors remains a critical challenge, especially during takeover scenarios where the human driver must re-assume control of the vehicle. This review paper focuses on the engineering and human-centred design of takeover requests (TORs) within Level 3 autonomous vehicles, emphasizing the importance of seamless transitions between automated driving and manual control. We explore the concept of the Operational Design Domain (ODD), which dictates the specific conditions under which an AV may safely operate, and contextualize its role. Through a comprehensive analysis, we highlight how monitoring both the internal and external environment, and improving human-machine interfaces through the design of takeover requests (TOR), play pivotal roles in ensuring that transitions are safe and efficient. We argue for the necessity of integrating detailed human factors and ergonomic considerations to foster a human-centred approach in AV design. We aim to establish a symbiotic relationship between human drivers and autonomous systems, ensuring that AVs not only function optimally within their designated ODD, but also maintain high safety standards during critical takeover moments.